FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PETANI TERHADAP USAHATANI MADU KELULUT DI KABUPATEN ACEH TIMUR - Varanita; Siti Balqies Indra; Muslimah (Bajang Institute, 2023)
This study aims to determine the effect of the amount of stup, income and farming experience on the interest of farmers in running a kelulut honey farm in East Aceh Regency. This research was conducted in East Aceh District. The sampling technique used was saturated sampling technique with a total sample of 30 kelulut honey farmers in East Aceh Regency. The data used in this study are primary data and secondary data. The data analysis method used in this study is Multiple Linear Regression Analysis, using the Classical Assumption Test (Normality Test, Multicollinearity and Heteroscedasticity) and Hypothesis Testing (F Test, t Test and R2 Test). The results showed that simultaneously the influence of the independent variables (Number of stup, income and farming experience) on the dependent variable (Farmers Interest). Partially, the number of stup factors (X1) did not have a significant effect on farmers' interest, while the income factor (X2) and farming experience (X3) had a significant influence on farmers' interests.